1991
DOI: 10.1002/1097-0142(19911101)68:9<1984::aid-cncr2820680923>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A tentative tumor–node–metastasis classification of thymoma

Abstract: To establish a tumor–node–metastasis (TNM) classification of thymoma, 207 thymoma patients seen at the First Department of Surgery, Osaka University, and the Second Department of Surgery, Nagoya City University, were evaluated. Lymphogenous and hematogenous metastases of thymoma were infrequent, but their frequency increased with the duration of the course. Lymphogenous metastasis was observed in few cases, but it was considered to progress from anterior mediastinal lymph nodes to intrathoracic and then to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
10

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(97 citation statements)
references
References 3 publications
2
82
0
10
Order By: Relevance
“…21,24 The most important aspect of histologic tumor classifications is clinical relevance. However, the current study confirmed previous investigations 2, 3,10,11,16,25 that showed that tumor stage is the single most important prognostic factor in thymomas (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…21,24 The most important aspect of histologic tumor classifications is clinical relevance. However, the current study confirmed previous investigations 2, 3,10,11,16,25 that showed that tumor stage is the single most important prognostic factor in thymomas (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…Although the traditional staging system according to Masaoka et al 1 has proved to be a good system for prognosis that has not been replaced by a similar TNM classification, 2 there is still some confusion about the predictive value of different histologic classifications . The 2 classification s most commonly used in recent years for thymomas are the traditional method based on cell shape and number of lymphocytes 3 and the histogenetic classificatio n based on epithelial cell morphology.…”
mentioning
confidence: 99%
“…Tanı anında %90-95 oranında lokalizedir ve bu nedenle primer tedavi cerrahi rezeksiyondur (2,3). En önemli iki prognostik faktör hastalığın evresi ve tam cerrahi rezeksiyondur (4)(5)(6).…”
Section: Timomaunclassified